Algal study in springs and streams from Shaqlawa district, Erbil Province, Iraq I- Euglenophyta (Baghdad Science Journal, 2022)
In an intensive study of the various species of the Euglenophyceae under different environmental conditions, the algal samples were collected monthly in twelve springs and six related streams from September 2019 to August 2020 within Shaglawa district-Erbil Province in virgin areas for phycolimnological study. Twenty species of Euglenophyceaen are identified as a new record for the algal flora. These taxa consist of Colacium vesiculosum, Lepocinclis salina and L.wangi, Eutreptia viridis, Euglena chlamydophora, E. clavata, E. geniculata, E.  intermedia var klebsii, E. limnophila, E. oblonga, E. sociabilis, E. stellate and E. variabilis, Peranema sacculus, Phacus circumflexus, Ph. dangeardii, Ph. peteloti, Petalomonas mediocanella var disomata, Trachelomonas manginii, and T. volvocina var derephora. All of these new records are described and illustrated as much as possible. According to physicals and chemicals characteristics, water temperature varied from 14.942˚C to 18.475˚C, pH lies on alkaline side of neutrality, electrical conductivity ranged between (627.472-2092.306µs/cm) and high concentration of salinity recorded in Azarian spring.